PELATIHAN PEMBUATAN PERANGKAT KOMPOSTER UNTUK PRODUKSI PUPUK ORGANIK - Suharno Suharno; Puguh Sujarta (LPPM Uncen, 2021)
The garbage is a problem in human life in the world. The problem of garbage to exists in our environment, due to the production of garbage every day. The production of organic fertilizer requires technology aimed at producing environmentally friendly and good quality organic fertilizer by making a composter kit. The objective of this community service is to introduce the training program for making Composter Kit for organic fertilizer production. This activity was held on September 2020 at SMA Negeri 2 Skanto Keerom. The target audience involved in this activity is high school students. The selection of target audiences is based on the duties and obligations of students to develop Adiwiyata High School that loves the environment. The methods used in this activity are lectures, simulations and practices on making composter kits for organic fertilizer production. The conclusion was that the participants were enthusiastic and knew the results of various organic waste products, both liquid and solid, which were produced by the composter device they made. Based on the results of the evaluation, it shows that the level of participant satisfaction is high when viewed from the percentage of all aspects. Keywords: organic waste; composter kit; adiwiyata; environment; keerom